Surface chemistry of colloidal surfactant-free gold nanoparticles generated by laser ablation. Issue 20 (January 2020) - Lévy, A; De Anda Villa, M; Gaudin, J; Amans, D; Blanchet, V; Boudjada, F; Bozek, J D; Grisenti, R E; Lamour, E; Laurens, G; Macé, S; Milosavljević, A R; et al.
Synopsis: Surface chemistry of gold nanoparticles produced by laser ablation in liquids has been investigated using synchrotron radiation and the X-ray Photoelectron Spectroscopy technique. Thanks to the recorded core-level and valence spectra, combined with a detailed analysis based on Bayesian statistical methods, the oxide presence and its proportion on the nanoparticle surface have been determined.